2005
DOI: 10.1007/s11060-005-9028-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy and adjuvant chemotherapy with Topotecan for patients with glioblastoma multiforme

Abstract: Concurrent chemoradiotherapy and an adjuvant chemotherapy with Topotecan is feasible at acceptable toxicity levels also for patients with a moderate performance status. The patients benefit from the improvement of the clinical symptomatic complex and, even with unfavourable prognosis factors, have a higher median survival in comparison to data published on similar groups of patients given only radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…24 CPT-11 and topotecan have also shown some efficacy in the treatment of glioma. [25][26][27] However, low levels of efficacy when administered as a single agent and major toxicities such as colitis and interstitial pneumonia potentially limit their use for this purpose. 28,29 CKD-602 is a potent topoisomerase 1 inhibitor that does not have the poor water solubility and toxicity of its parent drug, camptothecin.…”
Section: Discussionmentioning
confidence: 99%
“…24 CPT-11 and topotecan have also shown some efficacy in the treatment of glioma. [25][26][27] However, low levels of efficacy when administered as a single agent and major toxicities such as colitis and interstitial pneumonia potentially limit their use for this purpose. 28,29 CKD-602 is a potent topoisomerase 1 inhibitor that does not have the poor water solubility and toxicity of its parent drug, camptothecin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in children affected by malignant brain-stem tumors, the association of carboplatin [83], paclitaxel in continuous infusion [84], or a combination of multiple drugs such as VP16, ifosfamide, CDDP, dactinomycin [85], to radiation therapy did not improve the prognosis in terms of overall survival or progression-free survival. In patients affected by high-grade glioma (mainly glioblastoma) Yang, et al [86] experienced the association of procarbazine, CCNU and VCR plus radiotherapy, Klantke, et al [87] topotecan in continuous infusion plus hyperfractionated radiotherapy (total dose 45.5 Gy + 12.25 Gy), Stupp, et al [88] radiotherapy plus continuous daily temozolomide. These authors found a significant survival benefit with acceptable toxicity.…”
Section: Concurrent Chemoradiotherapymentioning
confidence: 99%
“…DFS: rezidivfreies Überleben; OS: Gesamtüberleben. [14]. Topotecan (0.5 mg/m 2 /d) was given simultaneously to radiotherapy as CVI over 21 days.…”
Section: Tabellementioning
confidence: 99%